2019
DOI: 10.1111/jcmm.14806
|View full text |Cite
|
Sign up to set email alerts
|

14‐3‐3ζ binds to and stabilizes phospho‐beclin 1S295 and induces autophagy in hepatocellular carcinoma cells

Abstract: Data from The Cancer Genome Atlas (TCGA) indicate that the expression levels of 14‐3‐3ζ and beclin 1 (a key molecule involved in cellular autophagy) are up‐regulated and positively correlated with each other (R = .5, P < .05) in HCC tissues. Chemoresistance developed in hepatoma cancer cells is associated with autophagy initiation. This study aimed to explore 14‐3‐3ζ’s role in regulating autophagy in HCC cells, with a focus on beclin 1. The co‐localization of 14‐3‐3ζ and beclin 1 was detectable in primary HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Elevated expression of 14-3-3 δ protein have been reported recently in head and neck squamous cell carcinomas [ 10 ], liver cancer [ 11 ], nonsmall cell lung cancer, colorectal carcinoma [ 12 ], and breast cancer [ 13 ]. In our previous study, we also found the level of 14-3-3 δ protein is elevated in cholangiocarcinoma, but the samples contained a large portion of intrahepatic CCA [ 14 ], the role and expression of 14-3-3 δ in the development of extrahepatic CCA has not been well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated expression of 14-3-3 δ protein have been reported recently in head and neck squamous cell carcinomas [ 10 ], liver cancer [ 11 ], nonsmall cell lung cancer, colorectal carcinoma [ 12 ], and breast cancer [ 13 ]. In our previous study, we also found the level of 14-3-3 δ protein is elevated in cholangiocarcinoma, but the samples contained a large portion of intrahepatic CCA [ 14 ], the role and expression of 14-3-3 δ in the development of extrahepatic CCA has not been well studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the HCC immune microenvironment will improve the development of immunotherapies. Interestingly, increasing evidence suggests that hypoxia affects components of the HCC immune microenvironment (23)(24)(25). Therefore, investigating the gene expression changes associated with hypoxia pathways might contribute to survival benefits for patients with HCC.…”
Section: Original Articlementioning
confidence: 99%
“…RNF216 interacts with and ubiquitinates Beclin 1 at lysine 48, thereby contributing to Beclin 1 degradation, while SLC9A3R1 and USP19 blocks ubiquitin-dependent Beclin 1 degradation by interacting with Beclin 1 and removing the K11-linked ubiquitin respectively (9, 10). Liu et al (11) found that Beclin 1, the core molecule of the Becn1-PIK3C3 complex, could be SUMO3-conjugated by PIAS3 predominantly at K380 and deSUMOylated by SENP3. Tang et al (12) reported that 14-3-3z bound to and stabilized phospho-Beclin 1(S295), and induced autophagy and chemoresistance in hepatocellular carcinoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al. ( 11 ) found that Beclin 1, the core molecule of the Becn1-PIK3C3 complex, could be SUMO3-conjugated by PIAS3 predominantly at K380 and deSUMOylated by SENP3. Tang et al.…”
Section: Introductionmentioning
confidence: 99%